2015
DOI: 10.1155/2015/740208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Ag Doping on Physical and Optical Waveguide Properties of Highly Oriented Sol-Gel ZnO Thin Films

Abstract: A sol-gel dip-coating process was used to deposit almost stress-free highlyc-axis oriented zinc oxide (ZnO) thin films onto glass substrates. The effects of low silver doping concentration (Ag/Zn < 1%) on the structural, morphological, optical, and waveguide properties of such films were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy, UV-Visible spectrophotometry, and M-lines spectroscopy (MLS). XRD analysis revealed that all the films were in single pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 48 publications
4
14
0
Order By: Relevance
“…The optical absorption edge exhibits a red-shift with the rise of Ag doping concentration. The observed band gap narrowing is due to the existence of Ag impurities in the ZnO cells, which is in agreement with literature [24,25,43]. Figure 9 exhibits the room temperature photoluminescence spectra (excitation wavelength 325 nm) of undoped and Ag-doped ZnO thin films.…”
Section: Optical Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…The optical absorption edge exhibits a red-shift with the rise of Ag doping concentration. The observed band gap narrowing is due to the existence of Ag impurities in the ZnO cells, which is in agreement with literature [24,25,43]. Figure 9 exhibits the room temperature photoluminescence spectra (excitation wavelength 325 nm) of undoped and Ag-doped ZnO thin films.…”
Section: Optical Analysissupporting
confidence: 88%
“…00-36-1451 [23]. This result indicates a high preferential c-axis orientation of ZnO crystallites [24][25][26][27]. The third peak observed at 2θ = 36.35 • is also very weak and it is from the plane (101).…”
Section: X-ray Diffraction Analysismentioning
confidence: 98%
“…This may be caused by the interaction of particles through the van der Waals force, which causes the molecules to interact and bond with each other. Our results are in a good agreement with those of Dehimi et al (2015), which showed that the particle size of ZnO increased when Ag dopant was added to the ZnO particles during annealing, at a temperature of 500 o C. Kusdianto et al (2017) also report that particle size increased after adding the Ag nanoparticles to the TiO2 matrix due to the metalinduced crystallization phenomenon and the coalescence of particles. Furthermore, the heat transfer among the ZnO may be enhanced by the presence of Ag nanoparticles.…”
Section: Resultssupporting
confidence: 91%
“…It can be seen that as the Cu doping increases, the average crystallite size increases while the microstrian decreases which refers to improvement of the crystallinty and the reduction of the defects due to the completely integration of Cu 2+ ions into the CdTe lattice. Such increase in the average crystallite size and decrease in microstain is reported for films that have smaller ionic radius dopants [28].…”
Section: Structural and Microstructure Characterizationsmentioning
confidence: 52%